Improved knowledge of COPD management through a health education intervention: A study at Vina Estetica Hospital, Medan - Roslenni Sitepu; Kartika Sari Rizki; Dicho Zhuhriano Yasli; Andry Simanullang; Frenky Jones Manurung (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive disease characterized by airflow obstruction that requires effective self-management. Health education is a crucial intervention to improve patient understanding of symptom management. This study aims to analyze the effect of health education on patients' knowledge regarding COPD management in the inpatient ward of Vina Estetica Hospital, Medan. Methods: This research employed a quasi-experimental design with a one-group pretest-posttest approach. Sampling was conducted using total sampling, including 32 COPD patients as respondents. Data were collected using a questionnaire and analyzed using the paired t-test. Results: Before the health education intervention, the majority of respondents had good knowledge (59.4%). After the intervention, all respondents (100%) achieved the good knowledge category. Statistical tests showed a significant effect of health education on increasing patient knowledge (p-value 0.000; t-count 4.605). Conclusion: Health education is effective in improving the knowledge of COPD patients. It is recommended that nursing services implement continuous health education programs to optimize patient care.